Technological breakthroughs and advancements in the application of mRNA vaccines: a comprehensive exploration and future prospects - Wei, Zhimeng; Zhang, Shuai; Wang, Xingya; Xue, Ying; Dang, Sheng; Zhai, Jingbo (Frontiers in Immunology, 2025)
mRNA vaccines utilize single-stranded linear DNA as a template for in vitro transcription. The mRNA is introduced into the cytoplasm via the corresponding delivery system to express the target protein, which then performs its relevant biological function. mRNA vaccines are beneficial in various fields, including cancer vaccines, infectious disease vaccines, protein replacement therapy, and treatment of rare diseases. They offer advantages such as a simple manufacturing process, a quick development cycle, and ease of industrialization. Additionally, mRNA vaccines afford flexibility in adjusting antigen designs and combining sequences of multiple variants, thereby addressing the issue of frequent mutations in pathogenic microorganisms. This paper aims to provide an extensive review of the global development and current research status of mRNA vaccines, with a focus on immunogenicity, classification, design, delivery vector development, stability, and biomedical application. Moreover, the study highlights current challenges and offers insights into future directions for development.